Renewable Geothermal Energy Explorations - Ismail, Basel I. (IntechOpen, 2019)
The geothermal resources of the Earth are enormous. The resource is considered to be an environmentally friendly clean energy source that could significantly contribute to the reduction of GHG emissions when utilized for electrical power generation or direct heating applications. The source of geothermal energy is the continuous heat energy flux flowing from the interior of the Earth toward its surface. Geothermal energy resources vary geographically, depending on the depth and temperature of the resource, the rock chemical composition, and the abundance of ground water. This book is the result of contributions from several experts and researchers worldwide. The introductory chapter highlights the principles of geothermal power generation using LEGE-ORC technology and presents a summary of the following book chapters. Due to its important utilization and future prospects, various interesting topics of research related to geothermal energy explorations are covered in this book. It is hoped that the book will become a useful source of information and basis for extended research for researchers, academics, policy makers, and practitioners in the area of renewable geothermal energy explorations.